L'amico irraggiungibile (Materiali di Estetica. Terza serie, 2016)
Our dean, Luigi Ambrosoli, used to talk me about Guido’s moral integrity, about his etical consistency of professor, about the high interest he was able to arise during his lessons, about his warmhearted relationship with his students.